Improving financial access in Africa: insights from information sharing and financial sector development - Simplice Asongu (African Governance and Development Institute (AGDI), 2017)
The study investigates interactions between information sharing offices, the coexistence of financial sub-systems and financial access. The empirical evidence is based on Quantile regressions in order to articulate countries with low, intermediate and high levels of financial access. The scope of the study is on 53 African countries for the period 2004-2011. The following main results are established. First, the positive association between “information sharing offices (ISOs)” and “formal financial sector development” consistently increases with improvements in initial levels of credit access. Second, the negative linkage between ISOs and “informal financial sector development” consistently decreases with increasing levels of credit access. In summary, we establish that the positive complementarity of ISOs and financial formalization is an increasing function of financial activity (or access to credit) whereas the negative complementarity of ISOs and financial informalization is a decreasing function of financial activity.
Keywords: G20; G29; L96; O40; O55; 330; Information Asymmetry; Financialization; Financial Access